Blockade of alanine-serine-cysteine transporter 2 ameliorates systemic lupus erythematosus by suppressing CD4+ T cell expansion and T follicular helper cell generation - Qianjin Lu (21981249) (2025)
RNA-seq of splenic CD4+ T cells from WT and Slc1a5-cKO mice at steady state (part 2)